Szkoły rzemiosł budowlanych. (Malbork : [s.n.], 1959)
Afisz inf. o zapisach na rok szkolny 1959/1960.
Keywords: Szkoły -- Polska -- Malbork -- 1945-1970.; Malbork (Polska) -- 1945-1970 -- druki ulotne